2022
DOI: 10.1007/s10570-022-04963-2
|View full text |Cite
|
Sign up to set email alerts
|

Oil structuring properties of electrospun Kraft lignin/cellulose acetate nanofibers for lubricating applications: influence of lignin source and lignin/cellulose acetate ratio

Abstract: In the present work, electrospun Kraft lignin/cellulose acetate nanostructures were produced, assessed and proposed as structuring or thickening agents of castor oil for lubricating applications. Solutions of Kraft lignins (KL) derived from different sources (eucalyptus, poplar and olive tree pruning) and cellulose acetate (CA) were prepared and used as feed for electrospinning. The rheological properties (shear and extensional viscosity), electrical conductivity and surface tension of KL/CA solutions influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…Similar evolution of the conductivity with polymer concentration have been reported previously for other biopolymers. [20,22] Figure 1a displays the log-log plot of the viscosity versus shear rate for CAb solutions at concentrations ranging from 1.5% to 20 wt.%. All the solutions showed a Newtonian behavior for concentrations lower than 7.5 wt.%, with viscosity values ranging between 0.009 and 0.169 Pa s. However, at higher polymer concentrations the flow behavior turned to shear thinning above a critical shear rate (see Figure 1a).…”
Section: Physico-chemical Properties Of Cab Solutionsmentioning
confidence: 99%
“…Similar evolution of the conductivity with polymer concentration have been reported previously for other biopolymers. [20,22] Figure 1a displays the log-log plot of the viscosity versus shear rate for CAb solutions at concentrations ranging from 1.5% to 20 wt.%. All the solutions showed a Newtonian behavior for concentrations lower than 7.5 wt.%, with viscosity values ranging between 0.009 and 0.169 Pa s. However, at higher polymer concentrations the flow behavior turned to shear thinning above a critical shear rate (see Figure 1a).…”
Section: Physico-chemical Properties Of Cab Solutionsmentioning
confidence: 99%
“…High porosity is one of the most striking characteristics of the electrospun lignin networks used as thickener agents, which roughly ranges from 50 to 70%, as well as their ability to adsorb or entrap vegetable oils in the voids (see for instance refs. [35,36]). As can be seen in Figure 9, the friction coefficient and the wear scar volume increase with the porosity of the electrospun lignin network.…”
Section: Effect Of Morphological Parameters On the Friction And Wear ...mentioning
confidence: 99%
“…Nevertheless, these chemical modifications usually require chemicals, solvents and/or catalysts that make the synthesis of biopolymeric thickeners and the subsequent oil structuring process relatively complex and not entirely environmentally friendly, despite the fact the final product is. Very recently, we demonstrated that nanostructures generated with electrospinning from non-modified biopolymers can be proposed as effective oil structuring agents [35,36]. The high porosity, small size and high surface/volume ratio of nanofibrous webs are able to induce the formation of three-dimensional networks with a superior capacity to promote physical interactions between the oil and the nanofibers stabilizing the colloidal system through the formation of a percolation network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetable-based oil, derived from renewable resources, is environmentally friendly with high biodegradability, providing excellent lubrication and extending the lifespan of machinery and equipment. Therefore, vegetable-based oil holds a distinct advantage in the lubricant field and deserves further research and development [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%